PENGARUH FDR, BOPO DAN TATA KELOLA TERHADAP RISIKO PEMBIAYAAN MURABAHAH PADA BPR SYARIAH DI JAWA TIMUR (Studi Kasus Pada BPR Syariah di Jawa Timur Sesuai Data Bank Indonesia Tahun 2012-2013) - Oktavina, Prawita; Koerniawan, Koenta Adji; Dianawati, Eris (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2015)
Murabahah financing is financing services in the form of buying and selling by installments. Sale and purchase agreement with the original price of the goods at the additional profit agreed. The seller must notify the cost and decide the level of profit as additional with customer Agreement (the buyer). Agreement buying and selling goods on the original price with the additional profit agreed. As a banking, financial risk would be important to concern, because this risk often encountered at several bank. The purpose of this study was to determine the effect of FDR (Financing to Deposit Ratio), OER (Operational Efficiency Ratio) and Good Corporate Governance to the risk of murabahah financing at BPR Shariah in East Java . The object of this study is 18 BPR Shariah in East Java according to data from Bank Indonesia at the year of 2012 - 2013. The methods used for testing is multiple regression analysis. The study results showed that independent variables FDR, OER and Good Corporate Governance with F-Test, simultaneously affect the risk of murabahah financing. The partially results by T-Test, FDR variable partially does not affect the significance value 0.985, OER partially effect the significance value 0.000 and Governance variable partially does not effect the significance value 0.679. Adjusted R Square value of 0.316 indicates that the risk of murabahah financing can be explained by the research variables of 31,6 %, while the rest is explained by other factors.